Development of Basic Movement Learning Through Traditional Games at Elementary School Level - Sapitri, Ista (Yayasan Sembilan Pemuda Indonesia, 2023)
The aim of this research is to analyze the development of basic movement learning through traditional games at elementary school level in cluster 3 of Lubuk Batang sub-district. This research was conducted at Gugus 3 Elementary School, Lubuk Batang District. The research used the research and development (R&D) method from Borg and Gall. The research subjects were 30 class V students at Gugus 3 Elementary School, Lubuk Batang District. Data collection techniques were carried out by means of observation, documentation studies, interviews and tests. Data analysis techniques are carried out qualitatively and quantitatively. Based on the development results, it can be concluded: (1) Can be used as a reference to improve students’ motor skills; (2) The resulting model has several variations using traditional games; (3) This model will increase children’s interest in participating, because the form of training is packaged in the form of a fun game; (4) Contribute to preserving national culture, especially traditional games; and (5) Contribution to educational science, especially in the field of sports.